Beauty and Limitations of Museums as Tools for Social and Cultural Reawakening in Nigeria - Oluwole, Ajayi (Àgídìgbo: ABUAD Journal of the Humanities, 2019)
Museum has been described as a powerful cultural centre for the community, a powerful institution which has a lot to add to the development of any nation. It is man-made feature that exists to converse historic collections and commemorate past events for tourists consumption (youell, 1998). Examples of these are louvre Museum in paris, France; Esie national Museum and Ife National Museum (both in Nigeria). As a tourist attraction, it has a lot to do in promoting and ensuring sustainable tourism. It is a common feature in developed countries where several of them may be found in one town no matter the size of the town (Aremu, 2001). Museum offer much benefits to their visitors, their communities and the society as a whole. Museum as educational and institutional establishment, offers unparalleled opportunities for self-directed learning and exploration by people of diverse ages, interest, background and abilities. They are public gathering places where visitors can be entertained, inspired and introduced to new ideas.